Analysis, design and development of web-based thesaurus manager prototype for Philippine medical thesaurus administrator component - Cepillo, Kinchan D. (2004)
The world of medicine is a vast repository of information designed to help the lives of people. And medical professionals in the Philippines that include doctors, nurses, medical technicians, and the likes are exposed on a daily basis to various medical terms. The Philippine Medical Thesaurus is an attempt for medical terms to be stored, organized and managed.